مستوى الكفايات التدريسية لدى أساتذة التربية البدنية و الرياضية و علاقتها بتحقيق الكفاءات المهارية - خوصة, جمال; عياد, مصطفى; قويدر, العيد (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت الدراسة الى معرفة على مستوى الكفايات التدريسية لدى أساتذة التربية البدنية و الرياضة و علاقتها بتحقيق الكفاءات المهارية لدى تلاميذ الطور المتوسط في ظل التدريس بمنهاج الجيل الثاني، و اعتمد الباحث على المنهج الوصفي في الدراسة نظرا لطبيعة الموضوع، و تم استخدام استبيان لقياس الكفايات التدريسية و استبيان لقياس الكفاءات المهارية، حيث قدرت عينة الدراسة ب 30 أستاذ لمادة التربية البدنية في مرحلة التعليم المتوسط تم اختيارهم بطريقة عشوائية، حيث توصلت نتائج الدراسة الى أن مستوى الكفايات التدريسية مرتفع و أنه توجد علاقة ارتباطية موجبة بين الكفايات التدريسية و تحقيق الكفاءات المهارية لدى تلاميذ الطور المتوسط في ظل التدريس بمنهاج الجيل الثاني. Abstract : The study aimed to find out the level of teaching competencies among teachers of physical education and sports and its relationship to the achievement of skill competencies among intermediate stage students under the teaching of the second generation curriculum. The researcher relied on the descriptive approach in the study due to the nature of the subject. A questionnaire to measure skill competencies, where the study sample was estimated at 30 teachers of physical education in the intermediate education stage, who were chosen randomly Where the results of the study concluded that the level of teaching competencies is high and that there is a positive correlation between teaching competencies and the achievement of skill competencies among intermediate stage students under the teaching of the second generation curriculum.
لدى تلاميذ الطور المتوسط في ظل التدريس بمنهاج الجيل الثاني
مقال
Keywords: 1. الكفايات التدريسية ؛2. أستاذ التربية البدنية والرياضية؛3. الكفاءات المهارية،4 منهاج الجيل الثاني; Teaching competencies, skill competencies, second generation curriculum